1996
DOI: 10.1530/eje.0.1350198
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone response to growth hormone-releasing hormone varies with the hypothalamic-pituitary abnormalities

Abstract: We determined growth hormone (GH) and insulin-like growth factor I (IGF-I) levels after a 3 h infusion of escalating doses of growth hormone-releasing hormone (GHRH(1-29)) followed by a bolus injection in hypopituitary patients with marked differences in pituitary features at magnetic resonance imaging (MRI) in order to evaluate further the contribution of MRI in the definition of pituitary GH reserve in GH-deficient patients. Twenty-nine patients (mean age 14.5 +/- 4.0 years) were studied. Group I comprised 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our findings suggest that the severity of GHD is related not only to the number of pituitary hormone deficits, but also to the MRI findings. In this regard, we have previously shown that the GH response to a GHRH infusion in patients with pituitary stalk agenesis and ectopic posterior pituitary lobe was low regardless of whether they had IGHD or MPHD (22). We observed a significant correlation between the GH peak after provocative tests and serum IGF-I and IGFBP-3 concentrations as well as between IGF-I and IGFBP-3 at retesting.…”
Section: Discussionmentioning
confidence: 54%
“…Our findings suggest that the severity of GHD is related not only to the number of pituitary hormone deficits, but also to the MRI findings. In this regard, we have previously shown that the GH response to a GHRH infusion in patients with pituitary stalk agenesis and ectopic posterior pituitary lobe was low regardless of whether they had IGHD or MPHD (22). We observed a significant correlation between the GH peak after provocative tests and serum IGF-I and IGFBP-3 concentrations as well as between IGF-I and IGFBP-3 at retesting.…”
Section: Discussionmentioning
confidence: 54%
“…We are aware that the absence of pituitary stalk is associated with pituitary somatotrope hypoplasia, likely as the result of a defective GHRH stimulation. Nonetheless, testing with GHRH or GHRH plus arginine has shown various degrees of GH-releasing capabilities in these patients indicating the presence of functionally preserved somatotropes (14,21).…”
Section: Discussionmentioning
confidence: 96%
“…Use of this imaging technique after contrast medium administration in GHD patients has permitted the identification of residual vascular components of the pituitary stalk with significantly higher accuracy than with standard MRI (20). Interestingly, a GH response to GHRH and to GHRH plus arginine has been demonstrated in the great majority of GHD patients with a residual vascular connection, as opposed to a lack of response in patients with absent pituitary stalk (21,14). In other words, the GH responses to GHRH and to GHRH plus arginine were negatively correlated with the degree of pituitary stalk impairment as assessed by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown abnormal PP function, ranging from reduced vasopressin release after osmotic challenge, hypodipsia, or polydipsia (6) to persistent nocturnal enuresis or symptomatic CDI, in both familial (7) and sporadic cases of hypopituitarism associated with either isolated GH deficiency (IGHD) or multiple pituitary hormone deficiencies (MPHD) (6,8,9). Other studies which focused on the assessment of anterior pituitary function in patients with EPP have never reported water and electrolyte disturbances or CDI in these patient populations (1,2,(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%